Metadata creation and management in the preservation of digital information in selected libraries in Cape Town - Maruping, Lordwick (Department of Knowledge and Information Stewardship, 2024)
Metadata describes and organizes resources in the digital environment for users to discover. Metadata plays an integral part in the digital preservation of information resources even though inadequacies exist in its creation and management. Challenges that affect creation and management of metadata are metadata quality, which results from not applying metadata standards, and non-specialists creating metadata. The aim of study was to investigate how metadata is created and managed and the role it plays in the digital preservation of resources in selected libraries in Cape Town. The study was guided by the following research objectives: to determine how metadata is created and managed in the digital environment in selected libraries in Cape Town; to determine how metadata is managed in the digital environment in selected libraries in Cape Town; and to determine the principles and standards adopted in the creation and management of metadata in selected libraries in Cape Town. A qualitative approach and a comparative case study design was adopted. Qualitative data was collected from a sample drawn using purposive sampling from the target population of seven metadata librarians in selected libraries in Cape Town. Qualitative data were collected from seven metadata librarians through semi-structured interviews and document analysis. Documents that were analyzed are cataloguing manual, RDA cataloguing standards, cataloguing guidelines, and OCLC guidelines in selected libraries in Cape Town. Thematic content analysis was used to analyze the qualitative data. The study used themes such as demographic information, metadata creation, metadata for digital preservation, metadata standards, metadata management and metadata challenges in digital preservation. The findings of the study revealed that metadata librarians adhere to international standards and tools as AACR2, DDC, LCSH, Dublin Core, RDA and other standards for metadata creation and management of digital resources. The findings established that digital objects should have a unique identity number to manage the content on the digital resources. It was also found that metadata elements that are mainly created and managed in libraries are ISBN, author, title, publication information, pagination, subject headings, summary, and shelf number (call number). Challenges in the creation and management of metadata identified included the lack of security in library systems, lack ICT skills among librarians, and the lack of information on resources to catalogue. The overall findings revealed that metadata librarians performed descriptive metadata only in libraries. It also revealed that authority control is one of the most important management functions of metadata to ensure the effective accessibility of records. Descriptive metadata is for printed books, e-books, maps, art, journals, theses and dissertations, digital objects, and audio-visual materials such as CDs and DVDs for display and discovery by their users. The conclusion drawn from this finding is that metadata librarians create and manage descriptive metadata and that libraries follow international standards and use internationally recognized tools when creating digital records. The study recommends that metadata librarians should be involved at all levels in the development of a new library management system (LMS). This will ensure that the lack of security in the library system should be overcome. The study also recommended that metadata librarians should get training on ICT skills that affect metadata creation and management through LIS school.